Construction of Convergent Sequence in Cone 2-Normed Spaces - Sadjidon Sadjidon; Mahmud Yunus; Sunarsini Sunarsini (LPPM Institut Teknologi Sepuluh Nopember, 2015)
We introduce an idea of convergent sequence in a cone 2-normed space. We show that the convergence in 2-normed spaces using the definition of 2-norm by considering its dual space. Then we construct the convergence in cone 2-normed space, particularly for l2-space.